Trends in home economics education : an analysis of curriculum documents in Zimbabwe and South Africa - Chamisa, Shylet (School of Education, 2014)
The purpose of this study is to analyse and discuss current trends in the construction and development of home economics subjects in South Africa and Zimbabwe, trends that reflect the direction that home economics is taking in the new millennium. Practical/pre-vocational subjects were introduced in secondary school curriculum for both general education and labour market reasons, that is, for the preparation of pupils to 'enter employment' and/or for 'self employment'. Over the years national education planners have debated over the future of practical/vocational subjects on the school curriculum. Many writers note that the concern of these groups is related to the challenges of technology and globalisation and general concerns for youth employment and poverty alleviation. As a result, far from phasing out from the secondary school education scene in Africa, technical and vocational subjects (correctly termed pre-vocational education) are offered along with academic subjects. They have undergone change in an attempt to better meet the needs of the labour market and the challenges that technology and globalization bring.